Integration of Social, Organizational, and Technological Factors to Improve the Effectiveness of Environmental Policies in Waste Management in Bima City - Sri Sumanti, Endang; Prasetya, Didik Dwi; Patmanthara, Syaad (Emerging Information Science and Technology, 2025)
Bima City faces serious challenges in waste management, characterized by low service covera- ge (53.16%), limited processing facilities, and low public awareness and participation. This study aims to comprehensively evaluate the waste management system in Bima City and formulate sustainable strate- gies by integrating social, organizational, and technological factors. The research approach is quantitative with Structural Equation Modeling (SEM) analysis of 200 respondents from the community, sanitation workers, and environmental managers. The conceptual model was developed by adapting the Human–Or- ganization–Technology Fit (HOT-Fit) framework and Sustainability Metrics dimensions that include po- licy, participation, community behavior, and infrastructure technology. The results showed that organizational factors and public policy significantly influenced the effectiveness of waste management (β = 0.36; p < 0.001). Community participation was the dominant factor with a di- rect influence on management effectiveness (β = 0.45; p < 0.001), while community behavior acted as a mediator between technology and system effectiveness (β = 0.32; p < 0.001). The Goodness of Fit value showed a statistically appropriate model (CFI = 0.957; TLI = 0.951; RMSEA = 0.039). This study empha- sized the importance of synergy between policy support, social participation, and technological infrastruc- ture in building a sustainable waste management system.